Rebranding Foto Produk UMKM Madu Riduwan Di Kelurahan Gebang Putih Kota Surabaya - Akmal Nugraha Ramadhan; Ika Sari Tondang (Universitas Katolik Widya Karya Malang, 2023)
This article discusses the process of rebranding the product photo of Madu Riduwan UMKM in Gebang Putih Village. Product photo rebranding is an important strategy in strengthening brand identity, increasing visual appeal, and achieving marketing success. Through photo analysis prior to rebranding and planning for photo concept selection, Madu Riduwan UMKM managed to produce more attractive, professional product photos and strengthen their brand image. The results of this product photo rebranding are expected to expand market reach, increase brand awareness, and build closer relationships with consumers.